ANALYSIS OF THE ASYNCRONOUS MOTOR IN STEADY-STATE REGIME WHEN TAKING INTO CONSIDERATION THE MAGNETIZATION CHARACTERISTIC AND THE VARIATION OF THE ROTOR RESISTANCE WITH SLIP (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
In this paper, the influence of saturation on the performance of asynchronous motors is studied. To this end, starting from the equivalent scheme, we take into account that the film–iLm characteristic is treated as a current-controlled nonlinear inductor, and the rotor resistor on a phase is modeled as a time-variable resistor; the asynchronous motor operating in steady-state behavior was analyzed. The simulations were done by the dedicated performance programs (elaborated by the authors): ACAP – Analog Circuit Analysis Program, CSAP – Circuit Symbolic Analysis Program, and, to compare the results, by the SPICE program. All these programs are based on the modified nodal equations and permit Fourier analysis of all current and voltage waveforms. Thus, we can compute any higher-order harmonics that appear in the time variations of these quantities. Analyzing the results, we conclude that, due to high-order harmonics in the current variations, losses increase and, consequently, the asynchronous motor's performance decreases (e.g., efficiency and power factor). The analysis of the saturation effect on an asynchronous motor in steady-state behavior can also be performed using the state equations, which can be integrated with one of the MATLAB integration routines.
Keywords: Induction motor; Steady-state behavior